Sustainability Modelling for Employment-focused Training Ecosystems for Young Adults with Disabilities - Ravindranathan, Reshmi; Usha, S.; Tommy, Robin; George, Smitha Rosemary (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Neurodivergent young adults face significant employment challenges globally, with unemployment rates reaching 80% in India. This study examines an innovative employment-focused training ecosystem for neurodivergent individuals, incorporating technological interventions and a gig economy model. Neurodivergent individuals are those whose brain functions differently in one or more ways than is considered standard or typical. Methods: A mixed-methods approach was employed, combining quantitative analysis of program outcomes with qualitative insights from stakeholders. The study utilized technology interventions for skill assessment, implemented a 5D clarity process-based training curriculum, and integrated a gig economy framework. Results: The study demonstrated notable success in employment outcomes, with a significant proportion of participants securing work within months of completion. Participants reported substantial gains in digital skills acquisition. Technological interventions for assessments revealed unique strengths in individuals that were not apparent through traditional methods. The gig economy model showed promise in providing flexible, suitable employment options for neurodivergent individuals. Conclusions: The innovative ecosystem demonstrates significant potential in creating sustainable employment opportunities for neurodivergent individuals, addressing key gaps in traditional training and employment models.